Psychosocial Development Description of Preschool-Aged Children - Livana PH; Esti Esti Mediastini; Yazid Basthomi (Global Health Science Group, 2020)
Ability to perform the task of development should be achieved by preschool children according to their development and growth stages. Stimulus is often prohibited or blamed resulting in children losing initiative, easy to feel guilty and not creative when they become adults. The study aims to determine the description of psychosocial development in preschool-aged children. Quantitative research with a descriptive analytic approach was conducted on pre-school children who live in the city of Kendal, Central Java, Indonesia. The research sample of 120 children. Data were collected using a questionnaire. Data were analyzed univariately and presented in a frequency distribution. The results of the analysis of the total questionnaire questions showed that 88% of children were categorized in normal psychosocial development and 12% were in deviant psychosocial development. The results of the study concluded that the majority of pre-school psychosocial development are in the normal category, however it still needs to be stimulated to achieve better growth and developmnet and prevent obstacle in the future.